Динамика стационарных структур в параболической задаче с отражением пространственной переменной - Белан, Е.П. (Кибернетика и системный анализ, 2010)
Досліджено динаміку стаціонарних структур у нелінійному оптичному резонаторі з перетворенням відображення в двовимірному оборотному зв’язку. Математичною моделлю системи є скалярне параболічне рівняння з відображенням просторової змінної та умовою Неймана на відрізку. Досліджено еволюцію форм структур та їх стійкість при збільшенні відрізка. Встановлено, що число стійких структур зростає при зростанні відрізка. Використано метод центральних многовидів та метод Гальоркіна. Properties of stationary structures in a nonlinear optical resonator with a lateral inversions transformer in its feedback are investigated. The mathematical description of optical structures is based on a scalar parabolic equation with an inversion spatial argument and Neumann’s conditions on a segment. The evolution of forms of stationary structures and their stability are investigated. A special emphasis is put on the cases when the segment is lengthened. It is proved that the number of stable stationary structures increases with lengthening the segment. The center manifold method and Galerkin’s method are used.